2023
DOI: 10.1186/s12885-023-10618-7
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of missense SNP of protein kinase C epsilon in HCV-induced hepatocellular carcinoma

Abstract: Background The protein kinase C (PKC) family of serine/threonine kinases contains more than ten isozymes that are involved in multiple signaling pathways, including cell cycle regulation and carcinogenesis. The PKCε isozyme is an oncogene known to be upregulated in various signaling pathways involved in hepatitis C virus (HCV)-induced hepatocellular carcinoma (HCC). However, there is no known association of missense SNPs in PKCε with this disease, which can be a potential biomarker for early di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Variants present in the regulatory domain tend to affect PKCε`s flexibility, leading to deviation in the ability of PKCε to make protein-protein interactions that might be associated with disease progression [ 32 ]. In a recent study it was indicated that the PRKCE variant rs1553369874 was associated with HCV-induced HCC [ 33 ]. However, so far, no published data has reported the association of these variants with the risk of cervical cancer in in vivo or in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…Variants present in the regulatory domain tend to affect PKCε`s flexibility, leading to deviation in the ability of PKCε to make protein-protein interactions that might be associated with disease progression [ 32 ]. In a recent study it was indicated that the PRKCE variant rs1553369874 was associated with HCV-induced HCC [ 33 ]. However, so far, no published data has reported the association of these variants with the risk of cervical cancer in in vivo or in vitro studies.…”
Section: Introductionmentioning
confidence: 99%